2022
DOI: 10.3390/children9060801
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Individual Variability in Gross Motor Development in Healthy Full-Term Infants Aged 0–13 Months and Associated Factors during Child Rearing

Abstract: The gross motor development of a typically developing infant is a dynamic process, the intra-individual variability of which can be investigated through longitudinal assessments. Changes in gross motor development vary, according to the interaction of multiple sub-systems within the child, environment, task setting, and experience or practice of movement. At present, studies on environmental factors that influence gross motor development in full-term infants over time are limited. The main aim of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…After participating in the play program for a 3-month period, healthy orphaned infants in this study were able to show wider intra-individual variability of gross motor developmental percentiles. The wide intra-individual variability was in line with previous longitudinal studies indicating that developing infants typically exhibit variability in terms of gross motor percentile from 3 to 13 months [ 11 , 12 , 13 , 33 , 41 ], while intra-individual variability of gross motor development in the control group was quite stable, similar to previous studies on orphaned infants who displayed narrow intra-individual variability [ 19 , 20 ]. The mean value of intra-individual variability within 12 months in the study of Prommin et al was 55.4 percentile, while the mean intra-individual variability within 3 months of the current study was 34.3 percentile ( Table 3 ).…”
Section: Discussionsupporting
confidence: 90%
“…After participating in the play program for a 3-month period, healthy orphaned infants in this study were able to show wider intra-individual variability of gross motor developmental percentiles. The wide intra-individual variability was in line with previous longitudinal studies indicating that developing infants typically exhibit variability in terms of gross motor percentile from 3 to 13 months [ 11 , 12 , 13 , 33 , 41 ], while intra-individual variability of gross motor development in the control group was quite stable, similar to previous studies on orphaned infants who displayed narrow intra-individual variability [ 19 , 20 ]. The mean value of intra-individual variability within 12 months in the study of Prommin et al was 55.4 percentile, while the mean intra-individual variability within 3 months of the current study was 34.3 percentile ( Table 3 ).…”
Section: Discussionsupporting
confidence: 90%
“…Presently, the most common motor skill assessment is the Alberta Infant Motor Scale (AIMS) which established norms for motor skill acquisition using a sample from Canada in 1992 (Piper et al, 1992). Internationally, researchers who used the AIMS consistently found that infants from their populations did not achieve milestones at the same ages as the infants from Alberta, motivating them to adjust or create their own norms (Kepenek-Varol et al, 2020;Manuel et al, 2012;Saccani & Valentini, 2013;Saccani et al, 2016;Størvold et al, 2013;Tupsila et al, 2020;van Iersel et al, 2020). Just as it was suggested in the early 1990s, we suggest again in 2023 that the established norms from 1992 may not necessarily be currently applicable, even for the same population.…”
Section: Discussionmentioning
confidence: 99%
“…This study identified the key factors as internal systems, the environment, task complexity, and movement experiences. Caution is advised regarding the use of baby walkers in typically developing infants during their first year of life due to potential negative impacts [ 14 ]. Therefore, predicting the age of independent walking in preterm infants remains a challenging and understudied area, likely due to the complex influence of neonatal characteristics and individual variations in motor proficiency.…”
Section: Introductionmentioning
confidence: 99%